A Study on Imprint Behavior of Ferroelectric Hafnium Oxide Caused by High‐Temperature Annealing. Issue 7 (8th March 2023) - Sünbül, Ayse; Lehninger, David; Lederer, Maximilian; Mähne, Hannes; Hoffmann, Raik; Bernert, Kerstin; Thiem, Steffen; Schöne, Fred; Döllgast, Moritz; Haufe, Nora; Roy, Lisa; Kämpfe, Thomas; et al.
Abstract : Hafnium oxide is found to be a favorable material for ferroelectric nonvolatile memory devices. Its compatibility with complementary metal–oxide–semiconductor processes, the relatively low crystallization temperature when zirconium‐doped, and the thickness scaling are among the advantageous properties of hafnium oxide. Different requirements must be fulfilled for different applications of hafnium oxide. Herein, high‐temperature annealing and operation conditions are analyzed in order to investigate nonvolatile memories for automotive applications. A strong imprint behavior (shift in coercive voltages) is observed after annealing hafnium–zirconium–oxide thin films at temperatures varied between 100 and 200 °C. The imprint behavior is a significant challenge in many applications. Therefore, to reduce/recover the undesirable imprint behavior caused by high‐temperature treatment, two different ways are successfully examined and delineated here: endurance cycling and applying high electric fields. Abstract : The imprint behavior of back‐end‐of‐line compatible hafnium zirconium oxide thin films for nonvolatile memory applications is investigated with various annealing conditions (100, 150, and 200 °C for 2, 3, and 12 h of annealing). The imprint is extracted from both endurance and retention characteristics. Additionally, the effective activation energy of the imprint mechanism in HZO is calculated.